Toward the role of social agency in explaining the personalization effect - Lindhaus, Maike; Bolin, Julia S.; Weßeling, Laura; Oest, Luisa; Dutke, Stephan (Frontiers in Psychology, 2024)
Personalizing written learning materials has been shown to enhance learning compared to conventional text. The aim of the present study was to investigate the role of social agency in explaining the personalization effect. For this purpose, a theory-based scale for measuring social agency was designed including four facets: conversational character, sympathy and emotional connection, explanatory effect, and task involvement. The results of two experiments with N1 = 66 university and N2 = 77 high-school students showed that personalized written learning materials compared to non-personalized learning materials were rated higher on the first and partly on the second facet of social agency. However, the personalized materials did not increase learning outcome measures. Consistently, no differences in the task involvement between persons learning with personalized and non-personalized materials were found. Results show that personalization in conversational style alone does not lead to an improvement in learning performance unless other factors intensify task involvement.